2010
DOI: 10.1158/0008-5472.can-10-0192
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Biological Characterization of Exon 4 KRAS Mutations in Human Cancer

Abstract: Mutations in RAS proteins occur widely in human cancer. Prompted by the confirmation of KRAS mutation as a predictive biomarker of response to epidermal growth factor receptor (EGFR)-targeted therapies, limited clinical testing for RAS pathway mutations has recently been adopted. We performed a multiplatform genomic analysis to characterize, in a nonbiased manner, the biological, biochemical, and prognostic significance of Ras pathway alterations in colorectal tumors and other solid tumor malignancies. Mutatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
218
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(235 citation statements)
references
References 46 publications
13
218
2
2
Order By: Relevance
“…Tumor samples with matched normal tissue were collected during routine clinical care with patient consent under an institutional review board-approved protocol and snap-frozen. Single-nucleotide polymorphism fingerprinting was used to ensure that all tumor samples were obtained from unique patients and correctly matched to normal tissue (28). To determine the copy number landscape of HNSCC, DNA from microdissected tumors was extracted and analyzed using the Agilent 1M Human Comparative Genomic Hybridization (CGH) microarray (aCGH).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor samples with matched normal tissue were collected during routine clinical care with patient consent under an institutional review board-approved protocol and snap-frozen. Single-nucleotide polymorphism fingerprinting was used to ensure that all tumor samples were obtained from unique patients and correctly matched to normal tissue (28). To determine the copy number landscape of HNSCC, DNA from microdissected tumors was extracted and analyzed using the Agilent 1M Human Comparative Genomic Hybridization (CGH) microarray (aCGH).…”
Section: Resultsmentioning
confidence: 99%
“…(12)(13) Validation of extended RAS assessment for predicting lack of response to panitumumab (24)(25) First evidence on the role of NRAS mutations in predicting resistance to anti-EGFR moAbs (20) First retrospective evidence of KRAS mutations impairing response to anti-EGFR moAbs (10) and causal relation establishment (11) First comprehensive dissection of the EGFR pathway to investigate biomarkers of response to anti-EGFR moAbs (9) First multideterminant analysis of coexisting molecular alterations in individual CRC (44) identify additional biomarkers of resistance that could account for the heterogeneity in clinical response. Sequencing studies revealed that although more than 80% of KRAS variants occur in exon 2 at codons 12 and 13, oncogenic mutations also affect KRAS codons 59, 61, 117, and 146 (16)(17)(18). Additional mutations of the NRAS isoform occur at codons 12, 13, and 61 in approximately 3% to 5% of colorectal cancer samples ( 19 ).…”
Section: Known Culpritsmentioning
confidence: 99%
“…The level of sensitivity that we observed is in keeping with other studies using the MassARRAY platform, and exceeds the sensitivity of standard DNA sequencing (approximately 20% mutant allele). [33][34][35][36][37] Standard DNA input was 10 ng per multiplex well, but mutant alleles were readily detected with as little as 1 ng DNA per well ( Figure 1B). …”
Section: Mass Spectrometry-based Mutation Detectionmentioning
confidence: 99%